BIOMECHANICAL ASPECTS OF ARTIC RESTORATION OF CENTRAL INCISORS - Gasiuk, P.A. (World of Medicine and Biology, 2013)
As a result of comprehensive research interconnection condition for restoration of defects of hard tissues at the stage of preparation, we anticipate the establishment of a vestibular surface of the damaged tooth outer (enamel), rigidity and retention of items within the enamel. Creation of conditions and retention points in the vestibular and oral surfaces of the cutting edge of the tooth, which is subject to the restoration of the area increases the adhesion of a composite material with enamel.
Keywords: defect restoration; crown; preparation; enamel